Training in Group Decision Making in Situational Training Centers - Mitin, A.I. (Psihologo-pedagogičeskie issledovaniâ, 2018)
The article deals with the psychological and pedagogical problems of training situational centers (TSC) as a learning environment for group decision-making. TSC have a significant role to play in the process of formation of a new type of managerial personnel, managers for the "digital economy" and "digital state. Emphasizes the importance of workplaces as a Central element for the functioning of TSCs; in this case, the workplace is treated as an element of the educational environment in relation to two related subject areas – social management and education. The script approach at the organization of educational activity in TSC is described; the script of an educational task contains, in particular, characteristics and the description of the principles of work of the corresponding workplaces, and also methods of work of participants of studies (students, teachers, experts, game technicians, producers). The importance of forming a visual information image of the management situation for the collective work of students is emphasized. We consider the models of classes in the TSC (lecture-discussion, case-study, role play), as well as psychological, didactic, technological and organizational factors taken into account in these models. The problem of "Brainstorming" is considered as an example of communicative decision-making technology in the TSC. В статье рассматриваются психолого-педагогические проблемы учебных ситуационных центров (УСЦ) как среды обучения групповому принятию решений. УСЦ призваны играть значительную роль в процессе формирования управленческих кадров нового типа, управленцев для «цифровой экономики» и «цифрового государства». Акцентируется значимость автоматизированных рабочих мест как центрального элемента, обеспечивающего функционирование УСЦ; при этом автоматизированное рабочее место трактуется как элемент образовательной среды применительно к двум связанным предметным областям – социальному управлению и образованию. Описывается сценарный подход при организации учебной деятельности в УСЦ; сценарий учебной задачи содержит, в частности, характеристики и описание принципов работы соответствующих автоматизированных рабочих мест, а также методы работы участников занятия (обучающихся, преподавателей, экспертов, игротехников, режиссеров). Подчеркивается важность формирования визуального информационного образа управленческой ситуации для коллективной работы обучающихся. Рассматриваются модели проведения занятий в УСЦ (проблемная лекция, анализ конкретной ситуации, деловая игра), а также психологические, дидактические, технологические и организационные факторы, учитывающиеся в этих моделях. В качестве примера коммуникативной технологии принятия решений в УСЦ рассматривается задача «Мозговой штурм».